ITALY AFTER THE CRISIS: A CASE OF RECOVERYLESS CREDIT GROWTH - FORTE, Antonio (Theoretical and Practical Research in Economic Fields; Vol 2 No 2 (2011): TPREF, Volume II, Issue 2(4), Winter 2011, 2011)
In this study I compare the credit condition with the economic growth in Italy from January 2007 onward. Starting from the literature on the creditless recovery, I highlight the specific features of the Italian situation in which, notwithstanding the prolonged and deep economic crisis, the credit has persistently continued to grow. A comparison with the German case confirms the peculiar characteristics of the Italian condition. An econometric study supports this idea and, in order to depict this Italian economic situation, I propose a new expression: the recovery-less credit growth.